2013
DOI: 10.1080/13603116.2012.742143
|View full text |Cite
|
Sign up to set email alerts
|

Developing inclusive practice: teacher perceptions of opportunities and constraints in the Republic of Ireland

Abstract: There has been a significant policy shift from parallel systems of special and mainstream education in the Republic of Ireland towards provision underpinned by enabling legislation with a presumption for inclusion. The role of teachers in establishing inclusive learning environments is critical and it is generally accepted that inclusive practice relies to a large extent on teacher knowledge, skills, understanding, capacity and attitudes. This exploratory study aimed to gather information on teachers' attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 21 publications
3
67
0
7
Order By: Relevance
“…As such, the researchers of the present study intended to examine as well whether the learners with dyslexia and their counterparts who are without dyslexia could show a similar level of reading achievement given they receive the same combined strategy treatment. Shevlin, Winter and Flynn (2013) asserted that there has been a significant policy change in the special education systems in the Republic of Ireland towards the adoption of inclusion. The teacher's role in creating inclusive learning environments is essential, for the inclusive environments tremendously depend on having the teacher's knowledge, dispositions, cooperation, potentials, and attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the researchers of the present study intended to examine as well whether the learners with dyslexia and their counterparts who are without dyslexia could show a similar level of reading achievement given they receive the same combined strategy treatment. Shevlin, Winter and Flynn (2013) asserted that there has been a significant policy change in the special education systems in the Republic of Ireland towards the adoption of inclusion. The teacher's role in creating inclusive learning environments is essential, for the inclusive environments tremendously depend on having the teacher's knowledge, dispositions, cooperation, potentials, and attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Öğretmenler ve yöneticilerle yürütülen araştırmalarda öğretmenlerin ve yöneticilerin kaynaştırmayı genelde önemli ve yararlı buldukları, özel gereksinimli öğrencilerin bu uygulamadan yararlanmasının güç olduğunu düşündükleri, kaynaştırmaya yönelik tutumlarının ise ne tamamen olumlu ne de tamamen olumsuz olduğu (Avramidis ve Norwich, 2002;Batu, 1998;Blecker ve Boakes, 2010;Center ve Ward, 1987;Diken, 1998;Kaya, 2003;Leyser, Kappermann ve Keller, 1994;Myles ve Simpson, 1989;Uysal, 1995;Varlıer ve Vuran, 2006) görülmüştür. Ek olarak öğretmenlerin kaynaştırma ve özel eğitim konusunda bilgilerinin eksik olduğu, yeterli deneyimlerinin olmadığı (Babaoğlan ve Yılmaz, 2010;Berry, 2011;Demir ve Açar, 2011), kaynaştırma eğitimine yeterli zaman ayıramadıkları (Blecker ve Boakes, 2010;Horne ve Timmons, 2009;Saraç ve Çolak, 2012;Ünal, 2010), materyal ve fiziki ortamı yetersiz buldukları (Balo, 2015;Erişkin, Kıraç ve Ertuğrul, 2012;Kargın, Acarlar ve Sucuoğlu, 2003;Shevlin, Winter ve Flynn, 2013), bireyselleştirilmiş eğitim planı (BEP) hakkında yeterli bilgiye sahip olmadıkları ve BEP'i tam olarak uygulayamadıkları (Avcıoğlu, 2011;Çuhadar, 2006;Kargın ve diğerleri, 2003), aileler ile etkili ve yeterli işbirliği kuramadıkları (Demir ve Açar, 2011;Slavica, 2010); yöneticilerin ise kaynaştırma kavramı, kaynaştırmanın başarılı olabilmesi için kaynaştırma öncesi ve esnasında neler yapılması gerektiği konusunda yeterli bilgiye sahip olmadıkları sonucuna ulaşılmıştır (Pınar-Sazak ve Yıkmış, 2004). Sıralanan noktalarla birlikte özellikle öğretmenlerin ve yöneticilerin kaynaştırma uygulamasında yaşanan sorunlara ilişkin görüşlerinin incelendiği araştırma bulguları ise öğretmenler ve yöneticilerin kaynaştırma eğitimine uygun öğrencilerin seçilememesini (Lalvani, 2012;Saraç ve Çolak, 2012;Thorpe va Azam, 2010)…”
Section: Introductionunclassified
“…In other words, as Čagran and Schmidt (2011) claimed, students with EBD have a negative impact on their classmates' learning. No students learn well when discipline is undermined (Shevlin et al, 2013) and students with EBD need SEN to keep up with their classmates (Bornman & Donohue, 2013). Some teachers explained their attitudes by referring to the inflexibility of the strict, academically orientated curriculum (Avramidis & Kalyva, 2007;Gyimah et al, 2009;Shevlin et al, 2013).…”
Section: Students' Learning Outcomesmentioning
confidence: 99%
“…No students learn well when discipline is undermined (Shevlin et al, 2013) and students with EBD need SEN to keep up with their classmates (Bornman & Donohue, 2013). Some teachers explained their attitudes by referring to the inflexibility of the strict, academically orientated curriculum (Avramidis & Kalyva, 2007;Gyimah et al, 2009;Shevlin et al, 2013). In Grieve's (2009) study, teachers in Scotland reported that inclusion of students with EBD is difficult when combined with the schools' demands to produce measurable results and learning outcomes.…”
Section: Students' Learning Outcomesmentioning
confidence: 99%